Impact of Medication and Surgical Treatment on Cytokine Concentrations in Patients with Acute and Chronic Cholecystitis - Vityala, Yethindra (Asian Journal of Pharmaceutics (AJP), 2024)
Background: Cholecystitis is defined as the sudden inflammation of the gallbladder. Surgical intervention is usually necessary to treat this condition because of the difficulty in achieving non-surgical resolution and frequent recurrence without surgery. Objective: We aimed to assess the effect of medication and surgical treatment on cytokine concentrations in patients with acute and chronic cholecystitis who showed disease progression. Methods: A total of 133 patients with cholecystitis admitted to our hospital were categorized into two distinct groups. The acute cholecystitis group included 79 patients with acute cholecystitis, whereas the chronic cholecystitis group included 54 patients with chronic cholecystitis. An automatic immunoassay analyzer was used to assess the levels of cytokines interleukin 1 (IL-1), IL-4, IL-6, and tumor necrosis factor-alpha in the blood plasma. Results: IL-6 concentrations dramatically increased by a five-fold amount compared to those in the control group. IL-6 concentrations were considerably higher in patients with chronic cholecystitis (P < 0.01), but the concentrations of other cytokines were not significantly different (P > 0.05). The Evaluation of cytokines demonstrated that IL-6 levels increased by 88% in the acute cholecystitis group and 81% in the chronic cholecystitis group, with regard to sensitivity and specificity. In the chronic cholecystitis group, the level of serum IL-1β remained significantly elevated (P < 0.05) during discharge relative to its pre-treatment level; in contrast, other cytokines did not show significant changes (P > 0.05). Conclusion: IL-6 levels increase during inflammation, but treatment reduces cytokine concentrations and elevates IL-4 levels